Laboratory aspects of Lyme borreliosis. - Barbour, A G (1988)
Lyme borreliosis (Lyme disease), a common tick-borne disorder of people and domestic animals in North America and Europe, is caused by the spirochete Borrelia burgdorferi. Following the discovery and initial propagation of this agent in 1981 came revelations that other tick-associated infectious disorders are but different forms of Lyme borreliosis. A challenge for the clinician and microbiology laboratory is confirmation that a skin rash, a chronic meningitis, an episode of myocarditis, or an arthritic joint is the consequence of B. burgdorferi infection. The diagnosis of Lyme borreliosis may be established by (i) directly observing the spirochete in host fluid or tissue, (ii) recovering the etiologic spirochete from the patient in culture medium or indirectly through inoculation of laboratory animals, or (iii) carrying out serologic tests with the patient's serum or cerebrospinal fluid. The last method, while lacking in discriminatory power, is the most efficacious diagnostic assay for most laboratories at present.